Retardation of corrosion and tribological degradation of automotive materials in palm biodiesel / Sazzad Sharif - Sazzad , Sharif (2016)
Biodiesel has been promoted as a potential candidate to replace fossil fuel partially or completely. However, unstable fuel properties of biodiesel hinders its commercialization in automobile sector. Several remedial studies have been done to reduce material degradation by means of fuel alteration and metal surface modification. Recent studies with different additives doped biodiesel in reducing corrosion and tribological degradation are found to be more feasible. However, inhibition mechanism of additives are still unexplored and remain a further scope of study. The present study aims to investigate the effect of additives along with the inhibition mechanism in reducing corrosion and tribological degradation of automotive materials in palm biodiesel. Static immersion tests were conducted for corrosion study by exposing cast iron and low carbon steel coupons in palm biodiesel at 300 K and 353 K for 50 days in the presence and absence of additives (tert-butyylamine (TBA), Benzotriazole (BTA), Butylate-dhydroxytoluene (BHT), Pyrogallol (PY)). Tribological study was performed using ball-on-plate (steel ball and cast iron plate) high frequency reciprocating rig (HFRR) at 300 K with applied load of 75 N and frequency of 33 Hz. Tert-butyylamine (TBA), Benzotriazole (BTA), Butylated hydroxyamisole (BHA) and Tert-butyl hydroxyl quinine (TBHQ) were used for reducing tribological degradation. Effects of additive-doped biodiesel and its blends on exposed metals surfaces were examined by corrosion rate, inhibition efficiency, adsorption isotherm, thermodynamic function for corrosion study and specific wear rate, frictional coefficient, specific film thickness, lubrication regime, adsorption for tribological study. Metal surface characterization was done by Atomic Force Microscopy (AFM), Scanning Electron Microscope (SEM)/ Energy Dispersive Spectroscopy (EDS), X-ray Diffraction (XRD) and X-ray Photoelectron Spectroscopy XPS. The result shows that TBA doped biodiesel has fairly good corrosion inhibiting properties and increases with increasing TBA concentration. The higher inhibition efficiency could be attributed to the dominant physical adsorption which makes a protective layer over metal surface and prevents corrosion. In tribological study, results exhibit that TBHQ doped biodiesel derives a physicochemically adsorbed layer which suppresses the coefficient of friction and wear.